Bacterial Vaginosis - Wizal Putri Mellaratna; Della Vega Nisha Ayuna (Faculty of Medicine University of Malikussaleh, 2022)
Abstract Introduction: The vagina is normally inhabited by a number of organism, including Lactobacillus acidophilus, diphteroids, Candida and others. Normal vaginal flora contains aerobic and anaerobic bacteria, such as Lactobacillus species being the prominent microorganism with number more than 95% of the total bacteria present. Vaginal discharge can be classified into physiologic and pathologic discharge. Discussion: Bacterial vaginosis is a clinical syndrome caused by the alteration of Lactobacillus Sp that producing hydrogen peroxide with anaerobic bacteria that caused the disruption of the normal flora balance. Risk factors of bacterial vaginosis are sexual activity, vaginal douching, genetic, vaginal manipulation, smoking and using the intrauterine device. Diagnosis of bacterial vaginosis can be enforced by the gram staining and the calculation of Nugent score (positive diagnosis of bacterial vaginosis if nogent score 7-10). Amsel score can also be conducted if the Nugent score examination cannot be performed. Amsel score criteria consists of white homogen vaginal discharge, fishy odor (positive Whift test), pH > 4.5, and the finding of clue cell. The discovery of 3 citeria of Amsel can confirm the diagnosis of bacterial vaginosis. Treatment of bacterial vaginosis including systemic and topical therapy. Systemic antibiotic such as metronidazole and clindamycin is effective against the anaerob bacteria. Conclusion: bacterial vaginosis in an abnormal condition in the vagina caused by the overgrowth of anaerobic bacteria replacing the Lactobacillus hominis that caused the change of normal acidic pH vagina into alkaline. Amsel criteria and Nugent score can be requested to confirm the diagnosis of bacterial vaginosis. Proper diagnosis and treatment with metronidazole and clindamycin can improve the disease.